The effects of improved maize technology on household welfare in Buruku, Benue State, Nigeria - Victoria I. Audu; Goodness C. Aye (Cogent Economics & Finance, 2014)
This study was carried out to determine the welfare effects of improved maize technology in Buruku Local Government Area of Benue State, Nigeria. The study also examined the determinants of the adoption of improved maize technology. Structured questionnaires were used in collecting the primary data for the study. A multi-stage random technique was used in selecting 125 farm households for the study. The Logit and ordinary least square (OLS) models were used in analyzing the data. The OLS results show that adoption of improved maize varieties is positively and significantly related to household welfare and thus has contributed to moving farm households out of poverty. Other variables found to be statistically significant in explaining household welfare are education, household size, and landholding. The Logit results show that age, household size, off-farm income, and education were found to be significant in influencing farmers' adoption decisions. Some robustness checks were performed with different specifications of the Logit and OLS models as well as re-estimation with propensity matching score approach. Overall, the results are robust to different specifications.
Keywords: 330; maize; improved technology; household welfare